Efficacy and safety of ipragliflozin in patients with type 2 diabetes inadequately controlled on metformin: a dose‐finding study. Issue 5 (7th December 2012) - Wilding, J. P. H.; Ferrannini, E.; Fonseca, V. A.; Wilpshaar, W.; Dhanjal, P.; Houzer, A.
<x xml:space="preserve">Abstract</x> Aims Ipragliflozin is a novel, selective inhibitor of sodium glucose co‐transporter 2 (SGLT2 inhibitor) in clinical development for type 2 diabetes mellitus (T2DM) treatment. This study assessed the efficacy and safety of different doses of ipragliflozin. Methods In a 12‐week, multicentre, double‐blind, randomized, placebo‐controlled, dose‐finding study patients with inadequate glycaemic control on metformin monotherapy (≥1500 mg/day) were randomized to one of four ipragliflozin treatment groups (12.5, 50, 150 or 300 mg once daily) or placebo. Primary efficacy outcome was mean change from baseline in haemoglobin A1c (HbA1c) compared to placebo at week 12. Adverse events (AEs), vital signs and laboratory safety measurements were assessed. Results Ipragliflozin dose dependently decreased HbA1c from baseline to week 12 compared to placebo (−0.22, −0.34, −0.40 and −0.48% for ipragliflozin 12.5, 50, 150 and 300 mg, respectively). Decreases in body weight and blood pressure were observed for all ipragliflozin groups. AEs occurred in 39.7–51.4% of the ipragliflozin groups and 39.4% of placebo patients. Urinary tract infections (1.4–6.9 vs. 6.1%), genital infections (0–4.3 vs. 1.5%) and hypoglycaemia (0–5.9 vs. 3.0%) were similar in the ipragliflozin and placebo groups, respectively, without dose dependency. There were no clinically relevant effects on other safety measurements. Conclusions Ipragliflozin treatment improved glycaemic control when added to metformin therapy and may be associated with weight loss and reductions in blood pressure compared to placebo. No safety or tolerability concerns were identified at any of the tested doses supporting the further development of ipragliflozin at ≥50 mg doses in T2DM patients.